Wolfram syndrome: a monogenic model for diabetes mellitus and neurodegeneration - Fischer, Tom Tobias; Ehrlich, Barbara E. (Current opinion in physiology, 2020)
Wolfram syndrome (WS) is a rare, progressive disorder characterized by childhood-onset diabetes mellitus, optic nerve atrophy, hearing loss, diabetes insipidus, and neurodegeneration. Currently, there is no effective treatment for WS, and patients typically die between 30 and 40 years of age. WS is primarily caused by autosomal recessive mutations in the Wolfram syndrome 1 (WFS1) gene (OMIM 222300), which encodes for the protein wolframin (WFS1). This disorder is therefore a valuable monogenic model for prevalent diseases, particularly diabetes mellitus and neurodegeneration. Whereas reduced cell survival and secretion are known impairments causing WS, the underlying molecular pathways and the physiological function of WFS1 remain incompletely described. Here, we characterize WFS1 as a regulator of intracellular calcium homeostasis, review our current understanding of the disease mechanism of WS, and discuss candidate treatment approaches. These insights will facilitate the identification of new therapeutic strategies not only for WS but also for diabetes mellitus and neurodegeneration.